2023
DOI: 10.1001/jamanetworkopen.2023.30483
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Adolescents in Using Online Patient Portals

Bryan A. Sisk,
Alison L. Antes,
Christine Bereitschaft
et al.

Abstract: ImportanceMany health care systems offer adolescents access to health information through online patient portals, but few studies have explored how to engage adolescents in using and benefiting from online portals.ObjectiveTo determine how US children’s hospitals have attempted to encourage adolescent portal use, barriers to engaging adolescents, and ideal future goals for engagement.Design, Setting, and ParticipantsThis qualitative study performed structured qualitative interviews with informatics administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A qualitative study exploring strategies and barriers to engage adolescent patient portal use emphasised the need for content and functions tailored speci cally for adolescents, targeted promotions for the patient portal, and adolescent-speci c education about the patient portal (45). Yet, a pilot study reported that educating adolescents about their access to the patient portal, including privacy considerations and functionality, resulted in improved patient portal enrollment but not usage (42).…”
Section: Transition Into Adult Carementioning
confidence: 99%
“…A qualitative study exploring strategies and barriers to engage adolescent patient portal use emphasised the need for content and functions tailored speci cally for adolescents, targeted promotions for the patient portal, and adolescent-speci c education about the patient portal (45). Yet, a pilot study reported that educating adolescents about their access to the patient portal, including privacy considerations and functionality, resulted in improved patient portal enrollment but not usage (42).…”
Section: Transition Into Adult Carementioning
confidence: 99%
“…We interviewed 65 informatics administrators from multiple health systems across the United States. Our prior analysis of these interviews characterized the varying adolescent portal policies across the United States [ 16 ], as well as approaches to engaging adolescents in using the portal [ 25 ]. In this analysis, we aimed to identify guiding principles to inform the development of these policies in the future.…”
Section: Introductionmentioning
confidence: 99%